Barriers and facilitators of severe acute malnutrition management at Felege Hiwot Comprehensive Specialized Hospital, Bahir Dar, North West Ethiopia, descriptive phenomenological study. - Daniel Alelign; Netsanet Fentahun; Zeamanuel Anteneh Yigzaw (PLoS ONE, 2024)
Background Malnutrition is a clinical condition that affects all age groups, and it remains a major public health threat in Sub-Saharan Africa. As a result, this research aimed to investigate the barriers and facilitators of treating severe acute malnutrition at Felege Hiwot Comprehensive Specialized Hospital in Bahir Dar City, North West Ethiopia. Methods A descriptive phenomenological study was conducted from February to April 2021. The final sample size taken was fifteen based on data saturation. In-depth and key informant interviews were conducted with nine caregivers, three healthcare workers, and three healthcare managers supported by observation. A criterion-based, heterogeneous purposive sampling technique was used to select the study participants. Each interview was audio-taped to ensure data quality. Thematic analysis was done to analyze the data using Atlas. ti version 7 software. Results Two major themes and six sub-themes emerged. Barriers related to severe acute malnutrition management include subthemes on socio-economic and socio-cultural conditions, perceived causes of severe acute malnutrition and its management, and the healthcare context. Facilitators of severe acute malnutrition management include severe acute malnutrition identification, service delivery, and being a member of community-based health insurance. Conclusions Effective management of severe acute malnutrition was affected by a multiplicity of factors. The results reaffirm how socioeconomic and sociocultural conditions, perceived causes of severe acute malnutrition (SAM) and its management and the health care context were the major barriers, while able to identifying severe acute malnutrition, service delivery, and is a member of community-based health insurance were the major facilitators for SAM management. Therefore, special attention shall be given to SAM management.